1979
DOI: 10.1042/bj1770809
|View full text |Cite
|
Sign up to set email alerts
|

UDP-glucosyltransferase activity of housefly microsomal fraction

Abstract: Housefly UDP-glucosyltransferase activity towards p-nitrophenol was demonstrated in a system in vitro. The activity is localized in the microsomal fraction, requires UDP-glucose, is slightly stimulated by Mg2+ and is activated optimally over a wide range of detergent concentration. Phenobarbital increases the enzyme(s) activity about 3-fold, with p-nitrophenol as substrate, which differs from the corresponding mammalian glucuronyltransferase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
1

Year Published

1983
1983
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 7 publications
2
9
1
Order By: Relevance
“…Also manganese and calcium can act as bivalent cation activators for UDP-glucosyltransfcrase of rat liver 191. Digitonin has been reportcd to activate rat liver UDPglucosyltransferase 2.5-fold towards bilirubin [9]. Also Triton X-I00 stimulates glucosidation of p-nitrophenol in the housefly preparation [15]. In our study neither sodium cholate nor sonication activated UDPglucosyltransferase in the microsomes of Leucoplzaea maderue fat body.…”
Section: Discussioncontrasting
confidence: 37%
See 2 more Smart Citations
“…Also manganese and calcium can act as bivalent cation activators for UDP-glucosyltransfcrase of rat liver 191. Digitonin has been reportcd to activate rat liver UDPglucosyltransferase 2.5-fold towards bilirubin [9]. Also Triton X-I00 stimulates glucosidation of p-nitrophenol in the housefly preparation [15]. In our study neither sodium cholate nor sonication activated UDPglucosyltransferase in the microsomes of Leucoplzaea maderue fat body.…”
Section: Discussioncontrasting
confidence: 37%
“…The pH optima of UDPglucosyltransferase from different animal sources are generally broad and lie near 7 or are slightly alkaline [7, 9, 171. The activation of UDPglucosyltransferase by magnesium is evident. The optimal concentration, 10 mM for microsomal enzyme of P. ur?7ericuna, is of the same magnitude as for other substrates and species [9,15,211. Also manganese and calcium can act as bivalent cation activators for UDP-glucosyltransfcrase of rat liver 191. Digitonin has been reportcd to activate rat liver UDPglucosyltransferase 2.5-fold towards bilirubin [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…UDPGT activity was determined according to Morello and Repetto (1979) as modiWed by Leszczynski et al (1992). The reaction mixture consisted of 1 ml of the aphid supernatant, 0.833 mM UDP-glucose, 0.167 mM p-nitrophenol, 16.7 mM MgCl 2 , and 0.8% Triton X-100 buVered to pH 7.5.…”
Section: Preparation Of the Enzymesmentioning
confidence: 99%
“…In insects, the glycosylation of small lipophilic compounds has been considered as a minor enzymatic detoxification mechanism for half a century (Ahmad et al, 1986;Brattsten, 1988;Després et al, 2007;Smith, 1962). Insect UGT enzyme activity has been investigated in the housefly Musca domestica (Morello and Repetto, 1979), in the fruitfly Drosophila melanogaster (Real et al, 1991), in the tobacco hornworm Manduca sexta (Ahmad and Hopkins, 1992), in the silkworm Bombyx mori , and in other insects (Ahmad and Hopkins, 1993b). These biochemical studies have shown that the insect UGT enzymes typically use UDP-glucose as the main sugar donor unlike vertebrate UGTs which mainly utilize UDP-glucuronic acid.…”
Section: Introductionmentioning
confidence: 98%